KITA ASOI Modal Dasar Guru Menyemai Prestasi di SMA Negeri 2 Pati - Mulyono, Mulyono (Jurnal Nispatti, 2023)
Achievement is the result of activities that have been carried out or carried out. Among high school students, at least two achievements need to be understood, namely academic and non-academic achievements. Regulations governing student development in achieving academic and non-academic achievements are contained in the Regulation of the Minister of National Education Number 39 of 2008 concerning Student Development. The Ministerial Regulation is a barometer for fostering academic and non-academic achievements. The problems of this best practice are: 1) how to implement the KITA ASOI technique as a basic capital for teachers to sow achievements at SMA N 2 Pati? 2) how are the results of student achievement at SMA Negeri 2 Pati after the implementation of KITA ASOI?, and 3) what is the impact. The implementation of problem-solving strategies consists of preparation, implementation of revolutionary actions, and evaluation. The preparation stage utilizes observation sheets and checklists. The revolutionary stage consists of providing catalysts, intensive guided practice techniques, and illustrations of idol figures. Meanwhile, the evaluation stage consists of reflection activities, observation, and interviews. The routine, consistent, and sustainable implementation of KITA ASOI can produce results in both academic and non-academic areas, for both students and teachers. The obstacles that must be addressed immediately are the difficulty in changing teachers' mindsets, the limited knowledge of both teachers and students, and the difficulty in attracting role models. Supporting factors come from the community, the 2013 Curriculum, schools, and existing regulations.